1990
DOI: 10.2527/1990.6882400x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary electrolyte balance on performance and blood parameters of growing-finishing swine fed in high ambient temperatures.

Abstract: A growing-finishing trial using 96 crossbred pigs (21.8 kg initially) was conducted to determine the effect of dietary electrolyte balance (EB = Na + K - Cl, meq/kg of feed) on rate and efficiency of weight gain, blood gases and whole blood Na and K concentration during high ambient temperatures. Dietary EB (25, 100, 175, 250, 325 or 400 meq/kg) was altered by the substitution of CaCl2 for CaCO3 or NaHCO3 for corn and soybean meal. Increasing EB during the grower phase (21 to 50 kg) increased feed intake and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 0 publications
3
18
0
1
Order By: Relevance
“…All pigs were pen mates prior to the feeding trial and no new pigs were introduced which could explain the lack of fighting or aggressive behavior. A tendency towards improved ADG was reported by Utley et al (1987) when electrolyte balance was maintained at 250 meq/kg while Haydon et al (1990) stated that 250 meq/kg was the optimal rate of NaHCO 3 to be added to the ration to maintain ADG through periods of hot weather. No such increase in ADG was found in the current study during the 14-day feeding period.…”
Section: Dietary Treatmentsmentioning
confidence: 76%
See 1 more Smart Citation
“…All pigs were pen mates prior to the feeding trial and no new pigs were introduced which could explain the lack of fighting or aggressive behavior. A tendency towards improved ADG was reported by Utley et al (1987) when electrolyte balance was maintained at 250 meq/kg while Haydon et al (1990) stated that 250 meq/kg was the optimal rate of NaHCO 3 to be added to the ration to maintain ADG through periods of hot weather. No such increase in ADG was found in the current study during the 14-day feeding period.…”
Section: Dietary Treatmentsmentioning
confidence: 76%
“…The animal's ability to appropriately handle this stress will have an effect on meat quality (Hambrecht et al, 2005;Küchenmeister et al, 2005). Heat stress, in particular, can upset the acid-base balance of an animal, whereas adding electrolytes to finishing diets can help increase feed intake and, in turn, keep rate of gain consistent through hot periods of the year (Haydon et al, 1990). Researchers (Ahn et al, 1992;Boles et al, 1993Boles et al, , 1994 have shown that 1 to 2% electrolytes fed prior to slaughter increased the initial muscle pH by slowing glycogen metabolism and improving pork color (Minolta b⁎).…”
Section: Introductionmentioning
confidence: 99%
“…Haydon et al (1990) indicated that urinary N decreased and deposition efficiencies of intake N and digestible N of growing pigs increased with the increase of dietary DEB levels. In the present study, the fecal N linearly decreased, while the DN, DN/IN and RN/IN linearly increased with the DEB increase.…”
Section: Resultsmentioning
confidence: 99%
“…Patience et al (1987) illustrated that the acid-base balance of growing pigs was affected by dietary electrolyte balance. Haydon et al (1990) used 96 crossbred growing-finishing pigs to determine the effect of DEB on blood gases and found that blood pH, HCO 3 , total CO 2 and BE excess increased linearly as dietary EB increased.…”
Section: Resultsmentioning
confidence: 99%
“…The biological influence of heat stress is impacted by duration of exposure to extreme temperatures (Renaudeau et al, 2007), night cooling (Xin and DeShazer, 1991;Patience et al, 2005), relative humidity (Huynh et al, 2005), diet composition (Jørgensen et al, 1996;Kerr et al, 2003), and genetics (Brown-Brandl et al, 2001;Sutherland et al, 2006), among others. In particular, ME content (Baldwin and Sainz, 1995;Rodrigues et al, 2012), protein and AA balance (Kerr et al, 2003;Spencer et al, 2005;Wolp et al, 2012), dietary additives (Zier-Rush et al, 2014) ,and mineral concentrations (Haydon et al, 1990;Kim et al, 2009) all affect responses to heat stress. To understand the relationships among variables, a mixed-effect linear model of absolute intake was also derived from the data set.…”
Section: Model Improvementmentioning
confidence: 99%